Kajian Pelaksanaan Standar Keselamatan Kerja di Era New Normal Pada Proyek Jalan di Kabupaten Maluku Tenggara - Fauzan A. Sangadji (Universitas Putra Indonesia YPTK Padang, 2023)
The impact of the Covid 19 pandemic was very large for business people, especially construction services. The implementation of work safety has also begun to change following the new normal era standards from the Indonesian government's covid task force. The application of work safety in the new normal era itself has not been well socialized to construction service business actors. This study intends to see how big the implementation of work safety in the new normal era is according to the Covid task force standards and other preventive measures according to the latest research. This study used a questionnaire distributed to one of the road projects in Southeast Maluku district. Questionnaires and interviews were carried out to see how the new normal era standards were implemented in the project. The results of the questionnaire were then tested using validity and reliability tests to see whether the data collected was valid and reliable or not. Then the results of the data are taken for the mean value of the total filling to see how big the variable is applied. Based on the research results, it was found that the provision of job insurance or health insurance is the biggest priority for construction service actors to prevent and maintain the health of workers in the project.